Photochemical tagging for rapid quantitation of unsaturated fatty acids by mass spectrometry - Ma, Xiaoxiao (Anal Chem, 2016)
Fatty acid (FA) profiling provides phenotypic information and is increasingly used in a broad range of biological and biomedical studies. Quantitation of unsaturated FAs with confident carbon-carbon double bond (C=C) location assignment is both sample and time consuming using traditional gas chromatography mass spectrometry analysis. In this study we developed a rapid, sensitive, and quantitative method for profiling unsaturated FAs without using chromatographic separations. This method was based on a combination of in-solution photochemical tagging of a C=C in FAs and a subsequent gas-phase de-tagging via tandem (neutral loss scan) mass spectrometry. It enabled quantitation of unsaturated FAs from various biological samples (blood, plasma, and cell lines). More importantly, quantitative information of FA C=C location isomers, which was traditionally overlooked, could now be obtained and applied to studying FA changes between normal and cancerous human prostate cells.